Front Cover: Stabilizing Metal–Organic Polyhedra (MOP): Issues and Strategies (Chem. Asian J. 18/2019). Issue 18 (29th August 2019) - Mollick, Samraj; Fajal, Sahel; Mukherjee, Soumya; Ghosh, Sujit K.
Abstract : Cage compounds : Metal–organic polyhedra (MOPs) are discrete, metal–organic molecular entities composed of edge‐sharing molecular polygons or connected molecular vertices that offer much promise as porous materials owing to their well‐defined structures and solution processability. More information can be found in the Minireview by Sujit K. Ghosh et al. onpage 3096 in Issue 18, 2019 (DOI:10.1002/asia.201900800 ).